Biofilm Producing Rhizobacteria With Multiple Plant Growth-Promoting Traits Promote Growth of Tomato Under Water-Deficit Stress - Haque, Md. Manjurul; Mosharaf, Md Khaled; Khatun, Moriom; Haque, Md. Amdadul; Biswas, Md. Sanaullah; Islam, Md. Shahidul; Islam, Md. Mynul; Shozib, Habibul Bari; Miah, Md. Main Uddin; Molla, Abul Hossain; Siddiquee, Muhammad Ali (Frontiers in microbiology, 2020)
Plant growth-promoting rhizobacteria (PGPR) not only enhance plant growth but also control phytopathogens and mitigate abiotic stresses, including water-deficit stress. In this study, 21 (26.9%) rhizobacterial strains isolated from drought-prone ecosystems of Bangladesh were able to form air–liquid (AL) biofilms in the glass test tubes containing salt-optimized broth plus glycerol (SOBG) medium. Based on 16S rRNA gene sequencing, Pseudomonas chlororaphis (ESR3 and ESR15), P. azotoformans ESR4, P. poae ESR6, P. fluorescens (ESR7 and ESR25), P. gessardii ESR9, P. cedrina (ESR12, ESR16, and ESR23), P. veronii (ESR13 and ESR21), P. parafulva ESB18, Stenotrophomonas maltophilia ESR20, Bacillus cereus (ESD3, ESD21, and ESB22), B. horikoshii ESD16, B. aryabhattai ESB6, B. megaterium ESB9, and Staphylococcus saprophyticus ESD8 were identified. Fourier transform infrared spectroscopy studies showed that the biofilm matrices contain proteins, polysaccharides, nucleic acids, and lipids. Congo red binding results indicated that these bacteria produced curli fimbriae and nanocellulose-rich polysaccharides. Expression of nanocellulose was also confirmed by Calcofluor binding assays and scanning electron microscopy. In vitro studies revealed that all these rhizobacterial strains expressed multiple plant growth-promoting traits including N 2 fixation, production of indole-3-acetic acid, solubilization of nutrients (P, K, and Zn), and production of ammonia, siderophores, ACC deaminase, catalases, lipases, cellulases, and proteases. Several bacteria were also tolerant to multifarious stresses such as drought, high temperature, extreme pH, and salinity. Among these rhizobacteria, P. cedrina ESR12, P. chlororaphis ESR15, and B. cereus ESD3 impeded the growth of Xanthomonas campestris pv. campestris ATCC 33913, while P. chlororaphis ESR15 and B. cereus ESD21 prevented the progression of Ralstonia solanacearum ATCC ® 11696 TM . In a pot experiment, tomato plants inoculated with P. azotoformans ESR4, P. poae ESR6, P. gessardii ESR9, P. cedrina ESR12, P. chlororaphis ESR15, S. maltophilia ESR20, P. veronii ESR21, and B. aryabhattai ESB6 exhibited an increased plant growth compared to the non-inoculated plants under water deficit-stressed conditions. Accordingly, the bacterial-treated plants showed a higher antioxidant defense system and a fewer tissue damages than non-inoculated plants under water-limiting conditions. Therefore, biofilm-producing PGPR can be utilized as plant growth promoters, suppressors of plant pathogens, and alleviators of water-deficit stress.